Houses of the unholy - Brubaker, Ed (Image Comics, Inc., 2024)
In this new tale, an FBI agent from the cult crime beat and a woman with a past linked to the Satanic Panic are drawn into a terrifying hunt for an insane killer hiding in the shadows of the underworld.